KEPUTUSAN PEMBELIAN PRODUK SAPA KOPI MENGGUNAKAN E-COMMERCE PADA LAYANAN PESAN ANTAR BERBASIS OJEK ONLINE - Jati Prastyo; Bambang Mursito; Istiqomah Istiqomah (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study is to examine purchasing decisions through online applications (e-commerce) on an online motorcycle taxi-based delivery service. This study uses a quantitative approach, namely by collecting data from respondents using a questionnaire. The number of samples is 100 people, calculated using the Slovin formula for buyers for three months. The sampling technique uses purposive sampling on consumers who have bought Sapa Kopi products through the Grabfood application. In testing multiple regression analysis using SPSS version 21, the calculated F value of 64.530 (p> 3.09) and a significance value of 0.000 (p 1.98) with a significance value of 0.000 (p 1.98) with a significance value of 0.000 (p 1.98) with a significance value of 0.017 (p